ANALISIS SMKK DAN SAFETY CULTURE MATURITY LEVEL TERHADAP PRODUKTIVITAS DAN KINERJA K3 - Johanes Tendy; Sembiring, Edison; Sugiarto, Sugiarto (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to analyze the perception of the implementation of the construction safety management system or more commonly known as SMKK and safety maturity level with productivity and OHS performance in the construction consultant industry. This study uses a quantitative approach with a survey method to collect data from respondents who have certain characteristics. The population in this study were construction experts working in construction service companies, with a total population of 267,837 people based on data from BPS and the Ministry of Public Works in 2023. Sampling was carried out using the Isaac & Michael formula with a significance level of 5%, so that a sample of 348 respondents was obtained. The sampling technique used was purposive sampling, with the criteria that respondents were part of the construction consultant team (team leader, expert, assistant expert, surveyor) using SmartPLS. The research measuring instrument also used a questionnaire distributed to Construction Workers (TKK) who had a Construction Expertise Certificate (SKK). The results of this study found that perceptions regarding the safety culture maturity level had a positive effect on work productivity and OHS performance, but perceptions regarding the implementation of SMKK had a negative effect on work productivity and had no effect on OHS performance.